2008
DOI: 10.1007/s10067-008-1039-1
|View full text |Cite
|
Sign up to set email alerts
|

Preference for weekly and monthly bisphosphonates among patients with postmenopausal osteoporosis: results from the Croatian PROMO Study

Abstract: The PROMO (preference for once monthly bisphosphonate) Study, conducted in seven hospital centres in Croatia between June 2007 and June 2008, was designed to analyse patient preference for weekly and monthly bisphosphonates in everyday clinical practice where the significant proportion of patients are not completely satisfied with the current osteoporosis treatment. Eligible participants were women with postmenopausal osteoporosis taking weekly bisphosphonates for the last 6 months. Those who agreed to be enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Most previous studies of bisphosphonate treatment preference and adherence have either used non-interventional designs [13,24,27], or they have been randomized studies that included questions about treatment preference but not about adherence [28][29][30][31][32]. Few studies have prospectively evaluated bisphosphonate treatment adherence [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of bisphosphonate treatment preference and adherence have either used non-interventional designs [13,24,27], or they have been randomized studies that included questions about treatment preference but not about adherence [28][29][30][31][32]. Few studies have prospectively evaluated bisphosphonate treatment adherence [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong evidence that monthly ibandronate is preferred by patients over weekly bisphosphonates (14)(15)(16)21). Similarly, a majority of patients stated that a monthly dosing regimen is more convenient and better fitted to their lifestyle.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a majority of patients stated that a monthly dosing regimen is more convenient and better fitted to their lifestyle. Moreover, several studies reported significantly lower incidence of adverse events associated with monthly compared to weekly bisphosphonates (14,24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MOBILE study showed that monthly oral administration of 100 mg and 150 mg ibandronate regimens were as effective as 2.5 mg daily oral ibandronate and well tolerated (17,18). In the recent studies, patients previously using weekly bisphosphonates (alendronate) reported improved satisfaction and preference with monthly ibandronate dosing (19)(20)(21). To collect further regional data on preference of patients for different dosing regimens of bisphosphonates, BONCURE (Bonviva for Current Bisphosphonate Users Regional European Trial) study evaluated the patients' satisfaction, preference and compliance, and tolerability of monthly ibandronate 150 mg in women with postmenopausal osteoporosis who had previously received weekly or daily alendronate or risedronate by using a validated satisfaction instrument relevant to treatment for osteoporosis (Osteoporosis Patient Satisfaction Questionnaire, OPSAT-Q).…”
Section: Introductionmentioning
confidence: 99%